2020
DOI: 10.11130/jei.2020.35.4.751
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Youth Employment in Sub-Saharan Africa: Should We Regulate the Labor Market?

Abstract: International trade is a determinative factor in reducing poverty and inequality, specifically through its role in stimulating job creation. Nevertheless, in several developing countries, international trade can lead to the destruction of jobs or the creation of less decent jobs, particularly for young people and women. The relationship between trade openness and employment has been widely discussed. Since the theories of Hecksher-Ohlin-Stolper-Samuelson and Viner, there has been no consensus regarding the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Several of the studies found inverse relationship between trade and employment (Dutt, et al, 2008;Campos-Vázquez & Rodríguez-López, 2011;Nchom & Udeorah (2021)). Others found positive effect of trade on employment (Polat & Uslu, 2011;Anyanwu, 2014;Kpognon, et al, 2020). Non-significant effect of trade on total employment was found in Yanikkaya, 2013;Rajesh & Subash, 2015).…”
Section: Empirical Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Several of the studies found inverse relationship between trade and employment (Dutt, et al, 2008;Campos-Vázquez & Rodríguez-López, 2011;Nchom & Udeorah (2021)). Others found positive effect of trade on employment (Polat & Uslu, 2011;Anyanwu, 2014;Kpognon, et al, 2020). Non-significant effect of trade on total employment was found in Yanikkaya, 2013;Rajesh & Subash, 2015).…”
Section: Empirical Literature Reviewmentioning
confidence: 95%
“…Non-significant effect of trade on total employment was found in Yanikkaya, 2013;Rajesh & Subash, 2015). However, Kim (2011) and Kpognon, et al (2020) attribute the effect of trade on employment on rigidity or flexibility of the labour market arguing that trade positively affects employment where labour market institutions are flexible. Several of the previous studies examined the effects of exports and import components of trade on employment (Herath, 2014;Akkus, 2018;Aigheyisi, 2019).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that because of economies of scale resulting from trade liberalisation, large firms are more efficient, productive and able to expand more quickly than small ones (Ha et al, 2020). Similarly, Kpognon et al (2020) found that trade openness had a negative and significant impact on youth employment in Sub-Saharan Africa's more rigid labour markets. In the same vein, Asaleye et al (2021) found that trade openness had a negative impact on employment and incomes in Nigeria's manufacturing and agricultural sectors.…”
Section: Introductionmentioning
confidence: 97%
“…In the region, poverty, as measured by the international poverty line, remains high. Furthermore, there has been a continuous rise in the absence of economic participation and opportunities, and unemployment, particularly among the youth (Kpongnon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%